Chemical Fingerprint and Metabolic Fingerprint of Danhong Injection by HPLC-UV and HPLC-MS - Zhou, Dan; Zhu, Yanrong; Guan, Yue; Quan, Wei; Li, Yuwen; Guo, Chao; Weng, Yan; Cui, Jia; Chen, Lei; Ding, Yi; Xi, Miaomiao; Wen, Aidong (Asian Journal of Chemistry, 2013)
Chemical fingerprint and metabolic fingerprint of Danhong injection and its raw materials (Radix Salviae miltiorrhizae and Flos carthami) were analyzed by HPLC-UV and HPLC-MS techniques. HPLC profiles, established as their characteristic fingerprints, were employed to assess the consistency and difference between Danhong injection and its raw materials. Ten batches of Danhong injections were analyzed under the same HPLC conditions. The results showed a good similarity. To determine the major constituents of Danhong injection for quality control, 19 major chromatographic peaks were characterized. Through comparison of the HPLC profiles of Danhong injection with its raw materials, it was found that they are greatly different, which indicated the changes of major constituents in the course of preparation procedure. In addition, to explore the in vivo metabolism of the major active constituents, the rat plasma was analyzed by HPLC techniques after intravenous administration of Danhong injection at different time intervals. The results indicated that danshensu, protocatechuic aldehyde, hydroxysafflor yellow A, rosmarinic acid and salvianolic acid B might be important for biological activity of Danhong injection. It could be concluded that chemical fingerprint combined with metabolic fingerprint is a useful means of controlling the quality and clarifying the possible mechanism of Danhong injection.